2009
DOI: 10.1111/j.1469-7610.2009.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control in anxious and healthy adolescents is modulated by incentive and incidental affective stimuli

Abstract: Background-Anxiety disorders are characterized by elevated, sustained responses to threat, that manifest as threat attention biases. Recent evidence also suggests exaggerated responses to incentives. How these characteristics influence cognitive control is under debate and is the focus of the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 39 publications
2
33
1
1
Order By: Relevance
“…Of particular interest here is that the antisaccade task can be modified by the substitution of the neutral peripheral target with an emotional stimulus (e.g., a sad or a happy face) (see Derakshan, Salt, & Koster, 2009, for evidence with dysphoric individuals; see also Hardin et al, 2009, for evidence with anxious adolescents). Specifically, Derakshan et al (2009) used facial expression (angry, happy, and neutral) in anti-and prosaccade tasks in order to examine the effects of subclinical depression (dysphoria) on attentional processing.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest here is that the antisaccade task can be modified by the substitution of the neutral peripheral target with an emotional stimulus (e.g., a sad or a happy face) (see Derakshan, Salt, & Koster, 2009, for evidence with dysphoric individuals; see also Hardin et al, 2009, for evidence with anxious adolescents). Specifically, Derakshan et al (2009) used facial expression (angry, happy, and neutral) in anti-and prosaccade tasks in order to examine the effects of subclinical depression (dysphoria) on attentional processing.…”
Section: Introductionmentioning
confidence: 99%
“…Normal developmental trajectories are defined by consistent age-indexed improvements in cognitive control capacity from infancy through adolescence to adulthood (Archer et al 2010a, b;Davidson et al 2006;Fair et al 2009;Stevens et al 2009). Somerville and Casey (2010) have indicated that the trajectory is determined by the context/extent in which control is necessary for regulatory behavior abilities whereby emotionally charged, rewarding or aversive contexts reduce control (Hardin et al 2009). Helpern et al (2011) have applied ''non-Gaussian water diffusion with diffusional kurtosis imaging,'' a technique that uncovers microstructural abnormalities, to study gray matter and white matter agerelated alterations in the prefrontal cortex of ADHD adolescents; comparisons with typically developing adolescents provided the aspect of assessing developmental trajectory.…”
Section: Adhd Developmental Trajectorymentioning
confidence: 98%
“…Very recent work has suggested that adolescents possess an enhanced ability to flexibly upregulate cognitive performance if an incentive is at stake. Work by Ernst and colleagues[42,43] used an antisaccade task to measure cognitive control behavior and promised a financial reward for accurate performance on some trials but not others. Results showed that promise of a reward facilitated adolescent cognitive control behavior more than for adults, a finding that has recently been extended to social rewards (e.g, happy faces) as well[44].…”
Section: Developmental Neurobiology Of Corticosubcortical Controlmentioning
confidence: 99%